Social Practices of Affiliates in the Digital Economy Era (Study on Shopee Affiliates on Social Media Instagram) - Tedjomurti , Febriandita; Mutiah, Mutiah (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2025)
The development of the digital economy has given rise to various new practices, one of which is the affiliate program offered by e-commerce platforms such as Shopee. The phenomenon of Shopee Affiliate, as one of the forms of the digital economy that is growing rapidly in Indonesia, cannot be separated from the social dimensions that underlie it. Although it appears to be an individual and pragmatic practice, Shopee Affiliate contains complex social dynamics. Therefore, this study aims to understand this phenomenon by applying Pierre Bourdieu's social practice theory approach to analyze how habitus, forms of capital, and the digital realm shape and reproduce affiliated practices among the general public. A qualitative-descriptive approach was employed in this study, involving 18 informants selected through the purposive sampling method and supplemented with literature reviews. This study demonstrates that participation in Shopee Affiliate is not merely a rational economic choice but a social practice shaped by social structure, digital habits, and access to capital.